Integrating STEAM into Elementary Classrooms: A Case Study of Elementary Teachers - Rosma Indriana Purba; Carmel Serafim Putri; Solomon Chheang (The Indonesian Institute of Science and Technology Research, 2026)
This study examines how elementary teachers new to Science, Technology, Engineering, Arts, and Mathematics (STEAM) perceive its relevance, implement it, and experience related challenges in classroom practice. Addressing the increasing demand for interdisciplinary, student-centered learning, the study employed a qualitative design using open-ended questionnaires administered to 12 purposively selected teachers in a private elementary school in North Jakarta. Data were analyzed through inductive thematic analysis to explore teachers’ perceptions, strategies, challenges, and professional learning needs. Findings indicate that teachers view STEAM as a holistic, future-oriented pedagogical approach aligned with child development and twenty-first-century competencies. However, implementation remains at an early stage, characterized by cautious, planning-focused experimentation. Teachers reported enhanced student engagement, improved collaboration, and the emergence of inquiry-based practices during integrated activities, despite challenges such as limited instructional confidence, lack of formal training, time constraints, and classroom management demands. The study provides empirical insight into how novice educators navigate STEAM integration without structured preparation and underscores the importance of sustained, practice-based professional learning. It concludes that effective and sustainable STEAM implementation requires alignment among classroom practice, professional development, and educational policy, supported by ongoing mentoring and collaborative learning structures to strengthen teachers’ confidence and professional identity.